Ardmore Studios, film workers and the Irish state, 1962–1964. Issue 2 (19th April 2022) - Murphy, Denis
Abstract : This article explores the most significant historic industrial dispute in Ireland's film industry, during the making of the UK film Of Human Bondage in the early 1960s. The conflict produced a prolonged standoff between Irish film trade unions and their much larger British counterparts, impacting on the viability of Ardmore Studios, established in 1957. Drawing on previously unexplored archival sources, this account reveals the delicate interplay between unions, employers and the Irish state in resolving the dispute. The timing of these events in the early 1960s demonstrates the international film industry's early adoption of a globalised production model, some decades before the 1980s-era developments more commonly associated with the globalisation framework. The events illuminate a crucial period in Irish film production history, underlining the importance of 'labour flexibility' in establishing Ireland as a viable production hub for mobile international film production .